An Approach to Rijndael Algorithm - Shiral, J. V.; Deshmukh, R. C.; Zade, J. S.; Potnurwar, A. (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
Rijndael or Advanced Encryption Standard (AES) is the most secure symmetric encryption technique and is available in many different encryption packages. The AES based on the Rijndael Algorithm is an efficient cryptographic technique that includes generation of ciphers for encryption and inverse ciphers for decryption. High security and speed of encryption and decryption is ensured by various operations. It has been standardized by the National Institute of Standards and Technology of the United States (NIST) and comprises three block ciphers, AES-128, AES-192 and AES-256 and it is adopted from Rijndael algorithm. This paper presents a encryption and decryption process of the rijindael algorithm. The paper also explains the comparative study of various rijindael algorithms with other algorithms based on the various parameters.